Overcoming Challenges and Promoting Positive Education in Inclusive Schools: A Multi-Country Study - Angel Deroncele-Acosta; Althia Ellis (Education Sciences)
Inclusive education faces significant challenges requiring deep understanding and comprehensive solutions. This study aims to establish a holistic framework for understanding the challenges in inclusive education, the core mission of inclusive schools, and the essential qualities of teachers. The methodology employed was qualitative, using the grounded theory method. A total of 59 experts from 13 countries participated in this study. Semi-structured asynchronous virtual interviews were conducted and analyzed using ATLAS.ti software (version 8). The results identified eight persistent challenges to inclusive education. In addition, positive education was highlighted as the fundamental core of inclusive schools, with emphasis on the development of learning, well-being, engagement, resilience, motivation, mental health, affective and social outcomes, creativity, and happiness. Finally, the integral profile of the inclusive teacher was defined based on a four-dimensional model. This groundbreaking study introduces a novel comprehensive framework that revolutionizes our understanding of the enduring challenges in inclusive education. Elucidating the core mission of inclusive schools and defining the essential qualities of inclusive teachers offers transformative insights. This study’s implications, future perspectives, and limitations provide a wealth of valuable information for policymakers, educators, and researchers, paving the way for innovative approaches and enhanced inclusive educational practices.